2016
DOI: 10.1002/hbm.23406
|View full text |Cite
|
Sign up to set email alerts
|

Networks underlying trait impulsivity: Evidence from voxel-based lesion-symptom mapping

Abstract: Impulsivity is considered a multidimensional construct that encompasses a range of behaviors, including poor impulse control, premature decision-making, and the inability to delay gratification. In order to determine the extent to which impulsivity and its components share a common network, we performed a voxel-based lesion-symptom mapping (VLSM) analysis in a large sample of patients (N=131) with focal, penetrating traumatic brain injuries (pTBI). Impulsivity was assessed using the Barratt Impulsiveness Scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 48 publications
(80 reference statements)
1
16
0
Order By: Relevance
“…Voxel-by-voxel analysis was used to calculate the statistical significance of performance difference between subjects with and without damage in a given voxel, using the Mann-Whitney test. To avoid spurious results due to low numbers of lesioned voxels, only voxels lesioned in at least 10 subjects were tested (Rorden et al, 2007 ; Medina et al, 2010 ; Handelzalts et al, 2019 ) and at least 10 adjacent voxels had to show a statistically significant impact on performance for a cluster of voxels to be reported (McDonald et al, 2017 ). To correct for multiple comparisons, voxels with values exceeding a permutation threshold of p < 0.05 were considered significant (Mirman et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…Voxel-by-voxel analysis was used to calculate the statistical significance of performance difference between subjects with and without damage in a given voxel, using the Mann-Whitney test. To avoid spurious results due to low numbers of lesioned voxels, only voxels lesioned in at least 10 subjects were tested (Rorden et al, 2007 ; Medina et al, 2010 ; Handelzalts et al, 2019 ) and at least 10 adjacent voxels had to show a statistically significant impact on performance for a cluster of voxels to be reported (McDonald et al, 2017 ). To correct for multiple comparisons, voxels with values exceeding a permutation threshold of p < 0.05 were considered significant (Mirman et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…Users also display a dysfunctional orbitofrontal cortex [59,60] and a smaller hippocampal size [56] with a maintained reduction in its volume in recent female abstinent users [61]. On the TBI front, recent studies have observed that focal penetrating injuries to the PFC lead to executive dysfunction and marked impulsivity, two traits implicated in addiction [62,63]. Also, high-level cognitive functions that regulate impulsivity, such as response inhibition, are compromised in diffuse axonal injury [64], a key feature of pathology seen following TBI [65,66].…”
Section: Physical Damagementioning
confidence: 99%
“…Notably, focal (i.e. penetrating) injuries to the PFC are associated with important behavioral deficits, as studies by Cristofori et al and McDonald et al have shown that damage to the PFC produces executive dysfunction and heightened impulsivity, two traits commonly implicated in drug and alcohol dependence 33, 34 . Therefore, regardless of TBI severity, damage to the PFC may be an important factor affecting the risk of SUDs in patients with a history of TBI.…”
Section: Neurocircuitsmentioning
confidence: 99%